Hydrolysis-resistant biodegradable melt-spun non-woven fabric as well as preparation method and application thereof

By using a dual -component leather core structure and adding auxiliary solutions in the biodegradable non -woven fabric, the problem of serious water solution of non -woven fabrics in high temperature and humidity is solved, and it is realized in the application of industrial filter elements. The effect of mechanical performance and durability.

CN119332413APending Publication Date: 2025-01-21SHANGHAI KINGFO IND CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202310881394.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing biodegradable non-woven fabrics are prone to hydrolysis in high temperature and humidity environments, resulting in a decline in mechanical properties and cannot meet the needs of filter elements and other applications.

Method used

Biodegradable melt-spun non-woven fabrics with a two-component sheath-core structure are added to the fiber core layer and fiber skin layers to improve the hydrolysis resistance of the non-woven fabrics by adding anti-hydrolysis agents, antioxidants, nucleating agents and processing aids. performance.

Benefits of technology

In high temperature and humidity environments, biodegradable melting spinning non -woven fabrics can maintain good mechanical performance and use durability performance, and are suitable for industrial filter elements and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004344744000000181
    Figure BDA0004344744000000181
  • Figure HDA0004344744010000011
    Figure HDA0004344744010000011
  • Figure HDA0004344744010000012
    Figure HDA0004344744010000012
Patent Text Reader

Abstract

The invention relates to the technical field of non-woven fabrics, in particular to a hydrolysis-resistant biodegradable melt-spun non-woven fabric as well as a preparation method and application thereof. The non-woven fabric is composed of biodegradable fibers, the fibers are of a two-component skin-core structure with a fiber core layer and a fiber skin layer, and the melting point of a core layer polymer forming the fiber core layer is higher than that of a skin layer polymer forming the fiber skin layer; the fiber further comprises an anti-hydrolysis agent, an antioxidant, a nucleating agent and a processing aid. The non-woven fabric provided by the invention has good degradation characteristic and hydrolysis resistance, can still maintain excellent mechanical property and use durability in a high-temperature and humidity environment, is uniform in cloth cover and high in air permeability, does not cause damage of fiber web pores caused by pricking points, and is more uniform in pore diameter. The preparation method is simple, refitting production can be carried out on traditional double-component spunbond equipment, and the equipment investment is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nonwoven fabrics, and in particular to a hydrolysis-resistant biodegradable melt-spun nonwoven fabric and a preparation method and application thereof. Background Art

[0002] The backing material used for the filter element is generally a non-woven fabric made of polyester (PET / PBT) and other raw materials. These materials usually have good air permeability, strength, stiffness and other properties, and are suitable for individual folding, or compounding with other materials by heat, glue, ultrasound and other methods to provide mechanical support. While meeting customer requirements, manufacturers also noticed that these materials are not degradable, especially after being compounded with other materials, it is very difficult to recycle these materials. Therefore, there is a need to develop a filter element backing material that can be completely biodegradable and meet customer expectations. To maintain the biodegradability of the final product, biodegradable materials are considered to be more acceptable materials from an environmental perspective, so the use of biodegradable materials instead of traditional petroleum-based resins is considered to be a feasible solution.

[0003] At present, the biodegradable materials on the market mainly include PLA, PBAT, PBS, PHA, PCL, PGA, etc. They are all ester compounds with ester (-COOR) functional groups on the molecular chain. They are easily degraded under the action of water, enzymes, etc., and then transformed by microorganisms, and finally become water and carbon dioxide. Biodegradable materials have their advantages in performance, practicality, degradability, safety, etc. At the same time, the synthetic raw materials of some biodegradable materials can be obtained by biomass fermentation extraction, reducing the use of fossil energy, which is in line with the concept of sustainable development. In particular, PLA materials can be biodegraded while also having good mechanical properties, stiffness, and heat resistance.

[0004] However, biodegradable materials have poor hydrolysis resistance and are prone to hydrolysis under high temperature and humidity, resulting in a decrease in mechanical properties and ultimately loss of performance. Therefore, typical non-woven fabrics made of biodegradable materials cannot be used in filter elements.

[0005] The present invention aims to solve the problem of developing a non-woven fabric based on biodegradable materials, and the biodegradable non-woven fabric is suitable for industrial filter elements. The applicant has developed a non-woven fabric based on biodegradable materials to solve this problem. This non-woven fabric has good hydrolysis resistance and maintains good mechanical properties and durability in a high temperature and humidity environment. Therefore, it can be used in filter elements and other applications.

[0006] At present, there are many studies on the application of biodegradable materials in non-woven fabrics, but there are fewer studies on improving the durability and hydrolysis resistance of biodegradable non-woven products.

[0007] Patent CN103741374A discloses a two-component coarse denier spunbonded filament nonwoven fabric, which involves biodegradable material PLA. The product has a unit area mass of 30-400g / m2, a longitudinal tensile force of 50-600N / 50mm, a transverse tensile force of 40-500N / 50mm, and an air permeability of 5000-1600L / m2 / s. Its main application is in the field of filtration, but it does not solve the problem of severe hydrolysis of PLA nonwoven products under high temperature and humidity.

[0008] Patent CN114318667A discloses a method for preparing ultra-soft biodegradable fiber non-woven fabrics, using PLA and PCL block copolymers as the cortex material of the bicomponent fiber to improve the problem of the hard feel of pure PLA non-woven fabric products, and its application is mainly in the field of sanitary products. It also does not solve the problem of hydrolysis of PLA non-woven fabric products under high temperature and humidity.

[0009] Patent CN114960177A discloses a biodegradable meltblown material with long-lasting electrostatic retention, which adds 0.2-1.0 parts of the anti-hydrolysis agent carbodiimide to improve the electrostatic retention and aging resistance of the meltblown cloth, extend the storage period of the degradable mask, and facilitate promotion and application. Regarding the evaluation of the electrostatic retention and aging resistance of the product, the patent does not provide the corresponding test data or results, and the product is a meltblown non-woven fabric, which is completely different from the non-woven fabric products, preparation methods and application fields provided by this patent.

[0010] Patent CN201180006421 discloses a polylactic acid composition, which uses a cyclic carbodiimide compound as an anti-hydrolysis agent and is blended with high optical purity PLA to obtain a resin composition that does not have free isocyanate compounds during manufacturing, has excellent hydrolysis resistance, and has low environmental load. It provides a method for improving the hydrolysis resistance of PLA, which is applied in the field of plastics. Summary of the invention

[0011] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a hydrolysis-resistant biodegradable melt-spun non-woven fabric and a preparation method and application thereof, which has the advantages of hydrolysis resistance and low environmental load, and is used to solve the problems in the prior art.

[0012] To achieve the above-mentioned purpose and other related purposes, one aspect of the present invention provides a hydrolysis-resistant biodegradable melt-spun non-woven fabric, which is composed of biodegradable fibers, and the fibers have a two-component core-skin structure of a fiber core layer and a fiber sheath, wherein the melting point of the core layer polymer constituting the fiber core layer is higher than the melting point of the sheath polymer constituting the fiber sheath; the fibers also include an anti-hydrolysis agent, an antioxidant, a nucleating agent and a processing aid.

[0013] Another aspect of the present invention provides a method for preparing the hydrolysis-resistant biodegradable melt-spun nonwoven fabric as described in the first aspect of the present invention, the preparation method comprising the following steps:

[0014] 1) mixing a core layer polymer, an antioxidant, an anti-hydrolysis agent, a nucleating agent and a processing aid uniformly to obtain a core layer raw material; mixing a skin layer polymer, an antioxidant, an anti-hydrolysis agent, a nucleating agent and a processing aid uniformly to obtain a skin layer raw material;

[0015] 2) melting, filtering, metering, distributing and extruding the core layer raw material and the skin layer raw material through a screw respectively to prepare a biodegradable primary fiber having a double-component core-skin structure with a fiber core layer and a fiber skin layer;

[0016] 3) After air cooling and air flow drawing and orientation, the nascent fibers are randomly and evenly laid on the forming mesh curtain under the action of a suction fan to obtain an unconsolidated nonwoven fabric;

[0017] 4) The unconsolidated nonwoven fabric is consolidated by hot air to obtain the nonwoven fabric.

[0018] Another aspect of the present invention provides a method for evaluating the hydrolysis resistance of a nonwoven fabric, using the hydrolysis-resistant biodegradable melt-spun nonwoven fabric of the first aspect of the present invention, the method for evaluating the hydrolysis resistance of the nonwoven fabric comprises the following steps:

[0019] a) According to the requirements of GB / T 24218.3, cut non-woven fabric strips along the MD direction;

[0020] b) Place the cut specimen in a container filled with 1.5±0.2 times its weight of pure water and seal it. To ensure that the specimen is completely immersed, a hydrophilic treatment agent of ≤1% may be added to the pure water, or manual intervention may be performed;

[0021] c) Place the sealed sample in a constant temperature and humidity chamber and age it for n days at 54±2℃ and 75±5%RH;

[0022] d) According to GB / T 24218.3, the initial breaking strength S0 and the breaking strength S0 after aging for n days were tested respectively. n ;

[0023] Calculate the sample breaking strength retention rate η n , where η n =S n / S0*100%, n-aging days.

[0024] Another aspect of the present invention provides application of the hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to the present invention in the field of industrial filtration.

[0025] Compared with the prior art, the hydrolysis-resistant biodegradable melt-spun nonwoven fabric of the present invention has the following beneficial effects:

[0026] 1) Compared with traditional polyester non-woven fabrics, the non-woven fabric of the present invention has good degradation characteristics and can be biodegraded in an industrial composting environment, meeting the composting degradation requirements of GB / T19277.

[0027] 2) Compared with typical biodegradable non-woven fabrics, the non-woven fabric of the present invention has good hydrolysis resistance and can still maintain excellent mechanical properties and durability in a high temperature and humidity environment.

[0028] 3) Compared with the traditional hot-rolled non-woven fabric, the non-woven fabric of the present invention has a uniform surface, high air permeability, no damage to the fiber mesh pores caused by puncture points, and a more uniform pore size.

[0029] 4) The nonwoven fabric of the present invention has a two-component skin-core composite structure, and the mechanical properties, thermal stability, and degradation rate of the nonwoven fabric can be flexibly designed by reasonably selecting the type of skin-core materials and / or controlling the proportion of each component to meet customer requirements.

[0030] The preparation method of the invention is simple, can be modified and produced on conventional two-component spunbond equipment, and requires little equipment investment. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Shown is a schematic diagram of a fiber cross section.

[0032] Figure 2 Shown is a cross section of a fiber under a microscope.

[0033] Figure 3 Shown is a schematic diagram of the sheath-core bicomponent fiber structure.

[0034] Figure 4 Shown as a hydrolysis-resistant biodegradable nonwoven fabric product.

[0035] Figure 5 Shown is a preparation flow chart of an embodiment of a hydrolysis-resistant biodegradable non-woven fabric. DETAILED DESCRIPTION

[0036] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0037] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps 1) and 2), which means that the method may include steps 1) and 2) performed sequentially, or may include steps 2) and 1) performed sequentially.

[0038] After a lot of exploration and experiments, the inventor of the present invention provides a hydrolysis-resistant biodegradable melt-spun non-woven fabric suitable for industrial filtration applications. Compared with the typical non-woven fabrics in the prior art, the non-woven fabric is composed of biodegradable fibers, and its properties enable the non-woven fabric made of it to obtain biodegradable properties that meet the requirements. The non-woven fabric is composed of biodegradable fibers, and the fibers have a two-component skin-core structure, that is, the fibers include a fiber core layer and a fiber skin layer. In particular, the fibers can further preferably be made of suitable skin materials and / or core materials to provide improved performance suitable for different filtration purposes. The non-woven fabric has good hydrolysis resistance and can still maintain good mechanical properties for a long time at high temperature and humidity. These properties are mainly due to the full orientation crystallization of the fibers and the addition of functional additives to the fiber materials, so that it has the desired mechanical properties in industrial filtration applications. The non-woven fabric surface is uniform and free of puncture points, avoiding the problem of filter pore damage caused by hot rolling and large air permeability resistance of the product, that is, it has good air permeability and uniform pore size. On this basis, the inventor completed this application.

[0039] Hereinafter, embodiments of the hydrolysis-resistant biodegradable melt-spun nonwoven fabric and the preparation method thereof of the present invention are specifically disclosed in detail.

[0040] 1) Weight

[0041] Determined according to GB / T 24218.1

[0042] 2) Breaking strength

[0043] Determined according to GB / T 24218.2

[0044] 3) Stiffness

[0045] Determined according to GB / T 18318.3

[0046] 4) Air permeability

[0047] Determined according to GB / T 5453

[0048] 5) Average pore size

[0049] Measured according to ASTM E1294-89

[0050] 6) Moisture content

[0051] Measured according to ASTM D6869

[0052] Hydrolysis-resistant biodegradable melt-spun nonwoven fabric

[0053] like Figure 1-4 In one aspect, the present invention provides a hydrolysis-resistant biodegradable melt-spun nonwoven fabric, which is composed of fibers having a bicomponent core-skin structure. The fiber is characterized in that the melting point of the core polymer constituting the fiber core layer is higher than the melting point of the skin polymer constituting the fiber skin layer.

[0054] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, the fiber core layer includes at least a core layer polymer, and may further include a modification aid, such as a combination of one or more of an anti-hydrolysis agent, an antioxidant, a nucleating agent, and a processing aid. The fiber skin layer includes at least a skin layer polymer, and may further include a modification aid, such as a combination of one or more of an anti-hydrolysis agent, an antioxidant, a nucleating agent, and a processing aid.

[0055] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, the core layer polymer is selected from any one of a first polylactic acid (PLA1) and a blend of a first polylactic acid and polyhydroxyalkanoate (PHA).

[0056] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, the skin layer polymer is selected from any one of a second polylactic acid (PLA2), polyhydroxyalkanoate (PHA), and polybutylene terephthalate-adipate (PBAT).

[0057] In some embodiments of the present invention, the PLA (first polylactic acid, second polylactic acid) selected by the core layer polymer and the skin layer polymer can be any one of a left-handed polylactic acid PLLA whose molecular chain structural unit is mainly a left-handed lactic acid unit, a right-handed polylactic acid PDLA whose molecular chain structural unit is mainly a right-handed lactic acid unit, or a mixture thereof. In addition, the PLA molecular chain structural unit can contain other copolymerization units. The copolymerization unit can be a unit such as a lactic acid unit, a dibasic acid, a diol, a lactone, a hydroxycarboxylic acid, etc., which has an optical activity different from the main structural unit of the molecular chain.

[0058] In some embodiments, for the core layer polymer, the optical purity of the first polylactic acid (PLA1) is preferably ≥95mol%, more preferably ≥98mol%, and further preferably ≥99mol%. The proportion of copolymerized units is preferably 5mol%, more preferably 2mol%, and further preferably ≤1mol%. The melting point of the first polylactic acid is preferably ≥155°C, more preferably ≥165°C, and further preferably ≥170°C. The weight average molecular weight of the first polylactic acid is preferably 10,000 to 200,000, more preferably 30,000 to 150,000, and further preferably 50,000 to 100,000.

[0059] In one embodiment of the present invention, the core layer polymer is a blend of a first polylactic acid and a polyhydroxyalkanoate (PHA), and the proportion of the polyhydroxyalkanoate (PHA) is ≤20%, preferably ≤10%, calculated based on the weight percentage of the fiber core layer.

[0060] In some embodiments of the present invention, the fiber core layer accounts for 35% to 80%, or 40% to 80%, preferably 40% to 70%, and more preferably 50% to 70% of the total fiber weight, calculated as the weight percentage of the components in the fiber.

[0061] In some embodiments of the present invention, the core layer polymer accounts for 80-99.35% of the weight of the fiber core layer, preferably 88.5-98.6% of the weight of the fiber core layer, calculated as the weight percentage of the component in the fiber core layer.

[0062] In some embodiments of the present invention, for the skin polymer, the optical purity of the second polylactic acid (PLA2) is preferably 80-98 mol%, more preferably 85-95 mol%. The proportion of copolymerized units is preferably 2-20 mol%, more preferably 5-15 mol%. The melting point of the second polylactic acid is preferably 115-165°C, more preferably 125-155°C. The weight average molecular weight of the second polylactic acid is preferably 10,000-200,000, more preferably 20,000-150,000, and further preferably 20,000-100,000.

[0063] In some embodiments of the present invention, the skin material can be polybutylene terephthalate-adipate (PBAT). Calculated by molar ratio, the proportion of BA (butylene adipate) units in PBAT is preferably 40-60 mol%, more preferably 42-55 mol%, and further preferably 45-50 mol%. The weight average molecular weight of PBAT is preferably 10,000-100,000, preferably 15,000-70,000, and further preferably 20,000-50,000.

[0064] In some embodiments of the present invention, the fiber cortex accounts for 20% to 65%, 20% to 60%, preferably 30% to 60%, and more preferably 30% to 50% of the total fiber weight, calculated as a percentage relative to the fiber weight.

[0065] In some embodiments of the present invention, the sheath polymer accounts for 80-99.35% of the weight of the fiber core layer, preferably 88.5-98.6%, calculated as a percentage relative to the weight of the fiber sheath.

[0066] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, the anti-hydrolysis agent is selected from one or a combination of monoepoxy glycidyl ester, diepoxy glycidyl ester, epoxy soybean oil, isocyanate glycidyl ester, monomeric carbodiimide, aliphatic carbodiimide and aromatic carbodiimide.

[0067] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, the antioxidant is selected from at least one of hindered phenol compounds, phosphite compounds, amine compounds and thioether compounds.

[0068] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, the nucleating agent is selected from at least one of an inorganic nucleating agent, an organic phosphate nucleating agent, an amide nucleating agent, a hydrazide nucleating agent, and polylactic acid with opposite optical activity.

[0069] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, the processing aid is selected from at least one of stearyl glyceryl, oleamide, ethylene bisstearamide, erucamide, barium stearate, calcium stearate, magnesium stearate, polyethylene wax, polyethylene glycol, and industrial white oil.

[0070] Generally, the addition of anti-hydrolysis agent can improve the hydrolysis resistance of biodegradable polymers, but it can also increase the viscosity of biodegradable polymers, increase the molecular weight, change the melting point and crystallization properties, and deteriorate the degradation properties. Therefore, it is necessary to strictly control the amount of anti-hydrolysis agent. In practice, the anti-hydrolysis agent accounts for 0.5% to 2% of the total weight of the fiber, preferably 0.8% to 1.5%.

[0071] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, the antioxidant is at least one of a hindered phenol compound, a phosphite compound, an amine compound or a thioether compound. Calculated by the weight percentage of the component in the fiber, the antioxidant accounts for 0.01-2% of the total weight of the fiber, preferably 0.03-1%.

[0072] Nucleating agents can provide crystal nuclei for the crystal growth of polymers, promote the formation of small and dense crystals in polymers under spinning conditions, and improve the crystallinity and dimensional thermal stability of fibers. It is worth noting that when polylactic acid with opposite optical activity is used as a nucleating agent, the crystal arrangement of polylactic acid molecular chains will form a stereoregular structure, which will increase the melting point of the polymer. Therefore, when selecting a nucleating agent for the fiber cortex, it is necessary to consider the increase in the melting point of the polymer. Calculated by the weight percentage of the component in the fiber, the nucleating agent accounts for 0.1% to 14% of the total weight of the fiber, preferably 0.5% to 8%;

[0073] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, the processing aid accounts for 0.04% to 2% of the total weight of the fiber, preferably 0.07% to 1% of the total weight of the fiber, calculated by the weight percentage of the component in the fiber.

[0074] In a specific embodiment, the nonwoven fabric may include the following fibers having the following components calculated in weight percentage relative to the weight of the fibers:

[0075] Core polymer 35.4% to 69.02%;

[0076] Cortical polymer 26.55% to 59.16%;

[0077] Anti-hydrolysis agent 0.8% to 1.5%;

[0078] Antioxidant 0.03%~1%;

[0079] Nucleating agent 0.5% to 8%;

[0080] Processing aids 0.07%~1%.

[0081] The anti-hydrolysis agent and the antioxidant are present in both the fiber core layer and the fiber sheath layer, and the types and amounts of the anti-hydrolysis agent and the antioxidant in the fiber core layer and the fiber sheath layer can be the same or different. The nucleating agent and the processing aid can be present in both the fiber core layer and the fiber sheath layer, or can be present only in the fiber core layer or the fiber sheath layer, and the types and amounts of the nucleating agent and the processing aid in the fiber core layer and the fiber sheath layer can be the same or different.

[0082] In the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, generally, the nonwoven fabric can be advantageously composed of fibers having the following properties:

[0083] The diameter of the fiber is 1 to 100 μm, preferably 10 to 50 μm, more preferably 15 to 30 μm. And / or,

[0084] The linear density of the fiber is 0.9 to 11.9 dtex, preferably 2.2 to 9.9 dtex, and more preferably 3.1 to 8.7 dtex.

[0085] Furthermore, the nonwoven fabric of the present invention may advantageously have:

[0086] Weight: 10~300g / m 2 , preferably 20 to 200 / m 2 , more preferably 30 to 150 g / m 2 , and / or a thickness of 0.15 to 1 mm, preferably 0.27 to 0.85 mm, more preferably 0.4 to 0.7 mm.

[0087] Tested under standard laboratory environment (20°C, 65% RH), the MD direction breaking strength is 0.6-3 times, 0.6-2.5 times, preferably 0.9-2.5 times, more preferably 0.9-2 times of the gram weight. The CD direction breaking strength is 0.5-2 times, preferably 0.9-1.8 times, more preferably 0.9-1.5 times of the gram weight; the MD direction stiffness is 0.5-2 times, preferably 0.9-1.5 times of the gram weight; the pore size is less than 75μm, preferably less than 40μm; the stiffness is ≥30mN, preferably ≥80mN, more preferably ≥120mN.

[0088] Meet the biodegradation standard of GB / T19277.

[0089] Preparation method of hydrolysis-resistant biodegradable melt-spun nonwoven fabric

[0090] The second aspect of the present invention provides a method for preparing the hydrolysis-resistant biodegradable melt-spun nonwoven fabric, the method comprising the following steps:

[0091] 1) mixing a core layer polymer, an antioxidant, an anti-hydrolysis agent, a nucleating agent and a processing aid in a proportion to obtain a fiber core layer raw material; mixing a skin layer polymer, an antioxidant, an anti-hydrolysis agent, a nucleating agent and a processing aid in a proportion to obtain a fiber skin layer raw material;

[0092] 2) melting, filtering, metering, distributing and extruding the core layer raw material and the skin layer raw material through a screw respectively to prepare a biodegradable primary fiber having a double-component core-skin structure with a fiber core layer and a fiber skin layer;

[0093] 3) After air cooling and air flow drawing and orientation, the nascent fibers are randomly and evenly laid on the forming mesh curtain under the action of a suction fan to obtain an unconsolidated nonwoven fabric;

[0094] 4) The unconsolidated nonwoven fabric is consolidated by hot air to obtain the nonwoven fabric.

[0095] In the method for preparing the hydrolysis-resistant biodegradable melt-spun nonwoven fabric provided by the present invention, in step 1), the moisture content of the polymer (core layer polymer or skin layer polymer) is 500 ppm, preferably 300 ppm, more preferably 200 ppm, and most preferably 100 ppm.

[0096] The polymer drying method can adopt the currently known drying methods, which can include vacuum rotary drying, drying tower drying, oven drying, etc. The vacuum rotary drying preferably has a drying temperature of 60-80°C, a vacuum degree of 0.06-0.1Mpa, and a drying time of ≥8h; the drying tower drying temperature is preferably 40-80°C, a dry air dew point of ≤-30°C, and a drying time of ≥8h; according to the type of polymer selected and the initial moisture content of the polymer, relevant technicians in this field know how to adjust the drying process conditions.

[0097] In step 1), the raw materials are as follows Figure 5 In a preferred embodiment, the polymer (core layer polymer or skin layer polymer) can be used as a carrier resin and mixed with an anti-hydrolysis agent, an antioxidant, a nucleating agent and a processing aid to pre-form a masterbatch.

[0098] Calculated by weight percentage of the raw material weight, the masterbatch accounts for 5% to 40%, preferably 5% to 30%. It should be noted that the raw materials, in addition to the masterbatch, also include certain polymers (core layer polymers or skin layer polymers), etc. By mixing the masterbatch with the remaining polymer, the mixing and dispersion can be more uniform.

[0099] In a specific embodiment, in step 1), part of the core layer polymer, antioxidant, anti-hydrolysis agent, nucleating agent and processing aid are first mixed in proportion to preform a core layer masterbatch; then the remaining part of the core layer masterbatch is mixed with the core layer polymer in proportion; wherein, calculated as a percentage by weight of the core layer raw material, the proportion of the core layer masterbatch is 5 to 40%; preferably 5% to 30%.

[0100] And / or, in step 1), firstly, a part of the skin polymer, antioxidant, anti-hydrolysis agent, nucleating agent and processing aid are mixed in proportion to preform a skin masterbatch; then the remaining part of the skin masterbatch is mixed with the skin polymer in proportion; wherein, calculated as a weight percentage of the weight of the skin raw material, the proportion of the skin masterbatch is 5-40%; preferably 5%-30%.

[0101] In step 1), in order to more conveniently control the addition ratio of the anti-hydrolysis agent and the nucleating agent, the mixture, in a preferred embodiment, can also be pre-made into an anti-hydrolysis masterbatch by blending the polymer (core layer polymer or skin layer polymer) as a carrier resin with the anti-hydrolysis agent, the antioxidant, and the processing aid, and pre-made into a nucleating masterbatch by blending the polymer (core layer polymer or skin layer polymer) as a carrier resin with the nucleating agent, the antioxidant, and the processing aid.

[0102] The steps for preparing masterbatch are as follows:

[0103] A) weighing the carrier resin, the modifying agent and the processing aid and mixing them evenly by a high-speed mixer;

[0104] B) injecting the mixed raw materials into a twin-screw extruder for blending and extrusion;

[0105] C) pelletizing the cooled material strands using a pelletizer to obtain the masterbatch.

[0106] In step A), the carrier resin selected for the core layer masterbatch is different from the carrier resin selected for the skin layer masterbatch, the carrier resin selected for the core layer masterbatch is the core layer polymer, and the carrier resin selected for the skin layer masterbatch is the skin layer polymer;

[0107] In step A), the modification aid is an anti-hydrolysis agent, an antioxidant, or a nucleating agent;

[0108] In step A), the modifying aid and processing aid selected for the core layer masterbatch and the modifying aid and processing aid selected for the skin layer masterbatch may be the same or different;

[0109] In step A), the speed of the high-speed mixer is ≥1000r / min, and the mixing time is ≥5min;

[0110] In step B), the aspect ratio of the twin-screw extruder is ≥40:1, the temperature of each zone of the screw is set to ≤190°C, and the vacuum degree is 0.04-0.1Mpa;

[0111] In step C), cooling can be carried out by water cooling, air cooling or the like, and the cooling length is ≥1.5 m.

[0112] As described above, relevant technicians in this field know how to adjust the relevant process according to the type of carrier resin and the formula ratio.

[0113] In step 1), the antioxidant accounts for 0.01% to 2% by weight of the fiber core layer raw material;

[0114] In step 1), the weight ratio of the anti-hydrolysis agent in the fiber core layer raw material is 0.5% to 2%;

[0115] In step 1), the mass ratio of the nucleating agent in the fiber core layer raw material is 0.1% to 14%;

[0116] In step 1), the weight ratio of the processing aid in the fiber core layer raw material is 0.04% to 2%.

[0117] In step 1), the weight ratio of the antioxidant in the fiber cortex raw material is 0.01% to 2%;

[0118] In step 1), the weight ratio of the anti-hydrolysis agent in the fiber cortex raw material is 0.5% to 2%;

[0119] In step 1), the mass ratio of the nucleating agent in the fiber cortex raw material is 0.1% to 14%;

[0120] In step 1), the weight ratio of the processing aid in the fiber cortex raw material is 0.04% to 2%.

[0121] In step 2), at least two melt preparation systems are included, that is, the system includes at least two sets of equipment including screw extruders, filters, metering pumps and melt pipes, a box containing two distribution pipelines and a spinneret assembly or die head containing two distribution systems to provide the core layer and skin layer of the fiber respectively.

[0122] In step 2), the function of the screw extruder is to convey and melt the polymer to obtain a uniform melt. The extruder may include a twin-screw extruder, a single-screw extruder, and the like. For the core layer raw material, the melting temperature is preferably 200-250°C. In some embodiments, the melting temperature may also be 200-230°C, 230-250°C, and the like. For the skin layer raw material, the melting temperature is preferably 140-230°C. In some embodiments, the melting temperature may also be 140-180°C, 180-200°C, 200-230°C, and the like.

[0123] In step 2), the function of the filter is to remove impurities in the melt and balance the pressure. The filter can be a plug-in filter, a double-cylinder filter, a vertical filter element filter, etc. The filter mesh is preferably 250-400 mesh. Since the shearing effect of the filter medium on the melt causes the melt to heat up and the material to degrade, the filter temperature setting should not be higher than the pipeline temperature setting temperature. In addition, it is necessary to control the pressure difference before and after the filter to avoid excessive pressure difference before and after the filter, which may cause material degradation and damage to the pipeline.

[0124] In step 2), the melt pipe plays the role of melt transportation and heat preservation. The heating method of the melt pipe can include jacketed pipe heat medium heating, electric blanket heating and the like.

[0125] In step 2), the metering pump is used to accurately meter and deliver the melt to ensure uniform extrusion of the nascent fibers. The metering pump may be a gear-type metering pump, a planetary-type metering pump, or the like.

[0126] In step 2), the function of the box is to keep the melt, components or die head delivered by the metering pump warm, and to evenly distribute the delivered melt to the components or die head. The box can be in the form of a hanger box, a manifold box, etc. The box heating method can be electric heating, heat medium heating, or heat medium and electric heating synergistic heating. Generally, the box temperature is higher than or equal to the pipeline temperature to ensure good spinning performance.

[0127] In step 2), the function of the assembly or die head is to further distribute the melt, even the melt pressure, and provide sufficient spinning pressure to extrude the nascent fiber through the spinneret. Usually, the assembly / die head includes a feed plate, a distribution plate, a filter screen, a sealing element, a spinneret, etc., and its form is usually circular, rectangular, etc.

[0128] In step 2), the melt preparation system may be further equipped with a booster pump to provide sufficient pressure before the pump to ensure accurate metering of the metering pump and avoid the occurrence of filament or fiber unevenness. The pressure before the pump is generally ≥0.3Mpa.

[0129] To ensure normal spinning, the spinning pressure is preferably 4-18 MPa. The diameter of the spinneret hole is generally 0.2-1 mm, preferably 0.3-0.8 mm. The aspect ratio of the spinneret hole is 3:1-10:1, preferably 4:1-8:1.

[0130] In step 2), the spun fiber has a skin-core structure, the ratio of the area of ​​the core layer to the area of ​​the skin layer is about 40 / 60 to 70 / 30, and the diameter of the spun fiber is preferably 0.22 to 1 mm, more preferably 0.32 to 0.8 mm.

[0131] In step 3), after the spun fibers are extruded, they pass through a slow cooling zone and are rapidly cooled by cold wind from the side wind. The slow cooling zone is used to prevent the cold wind from the lower end from blowing cold air on the plate surface and to provide a space for the spun fibers to relax stress to reduce fiber breakage. The height of the slow cooling zone is usually 0 to 100 mm, preferably 20 to 80 mm.

[0132] In step 3), the air cooling is provided by a side blowing device, and the side blowing temperature is 10-30°C, the wind speed is 0.1-6m / s, and the humidity is 65-97%RH. In some embodiments, the side blowing temperature can be 10-20°C, or 20-30°C, etc. The wind speed can be, for example, 0.1-1m / s, 1-2m / s, 2-3m / s, 3-4m / s, 4-5m / s, or 5-6m / s, etc.

[0133] In step 3), the fiber is mainly stretched by the airflow due to the friction between the airflow and the fiber surface to reduce the diameter of the fiber. This step preferably adopts a compressed air positive pressure stretching method. The stretching air pressure is 0.2-0.45Mpa. In some embodiments, the stretching air pressure can be 0.2-0.3Mpa, 0.3-0.4Mpa, or 0.4-0.45Mpa.

[0134] In step 3), the bicomponent fiber filaments are evenly spread into a web on a web-forming curtain by the suction action of a suction fan to obtain an unconsolidated fiber web.

[0135] In step 4), the unconsolidated fiber web is transported to a hot air oven through a mesh curtain. Under the penetration of hot air in the oven, the cortex of the two-component fiber melts and bonds with adjacent fibers to obtain a consolidated non-woven fabric without entanglements. The temperature of the hot air oven is 90 to 160°C. In some embodiments, the temperature of the hot air oven can be 90 to 110°C, 110 to 120°C, 120 to 130°C, 130 to 140°C, 140 to 150°C, or 150 to 160°C.

[0136] Method for evaluating the hydrolysis resistance of nonwoven fabrics

[0137] A third aspect of the present invention provides a method for evaluating the hydrolysis resistance of a nonwoven fabric, the method for evaluating the hydrolysis resistance of a nonwoven fabric comprising the following steps:

[0138] a) According to the requirements of GB / T 24218.3, cut non-woven fabric strips along the MD direction;

[0139] b) Place the cut specimen in a container filled with 1.5±0.2 times its weight of pure water and seal it. To ensure that the specimen is completely immersed, a hydrophilic treatment agent of ≤1% may be added to the pure water, or manual intervention may be performed;

[0140] c) Place the sealed sample in a constant temperature and humidity chamber and age it for n days at 54±2℃ and 75±5%RH;

[0141] d) According to GB / T 24218.3, the initial breaking strength S0 and the breaking strength S after aging n were tested respectively. n ;

[0142] Calculate the sample breaking strength retention rate η7, η 14 , η 28 , where η n =S n / S0*100%, n-aging days.

[0143] In a specific embodiment, in step c), the aging days can be, for example, 7 days, 14 days, or 28 days, and the corresponding breaking strength S7, S8 after aging for 7 days, 14 days, or 28 days in step d is S1, S2, S3, S4, S5, S6, S7, S8, S9, S10, S11, S12, S13, S14, S15, S16, S17, S 14 , S 28 In step d), the sample breaking strength retention rates η7 and η 14 , η 28 .

[0144] Under the hydrolysis resistance test conditions provided by the present invention, the breaking strength retention rate η in the MD direction is maintained for 28 days. 28 ≥50%, preferably ≥55%.

[0145] application

[0146] The fourth aspect of the present invention provides the application of the hydrolysis-resistant biodegradable nonwoven fabric of the present invention in the field of industrial filtration, wherein the industrial filtration field may be, for example, fan filtration, clean room filtration, automobile fresh air filter, HVAC, water filtration, composite backing material, etc.

[0147] In summary, the hydrolysis-resistant biodegradable non-woven fabric and its preparation method provided by the present invention have the following advantages:

[0148] 1) Compared with traditional polyester non-woven fabrics, the non-woven fabric of the present invention has good degradation characteristics and can be biodegraded in an industrial composting environment, meeting the composting degradation requirements of GB / T19277.

[0149] 2) Compared with typical biodegradable non-woven fabrics, the non-woven fabric of the present invention has good hydrolysis resistance and can still maintain excellent mechanical properties in a high temperature and humidity environment.

[0150] 3) Compared with the traditional hot-rolled non-woven fabric, the non-woven fabric of the present invention has a uniform surface, high air permeability, no puncture points to damage the interstices of the fiber web, and a more uniform aperture ratio.

[0151] 4) The nonwoven fabric of the present invention has a two-component skin-core composite structure, and the mechanical properties, thermal stability, degradation rate, etc. of the nonwoven fabric can be adjusted to meet customer requirements by reasonably selecting the type of skin-core materials and / or controlling the proportion of each component.

[0152] 5) The preparation method of the present invention is simple and can be modified and produced on conventional two-component spunbond equipment with low equipment investment.

[0153] The beneficial effects of the present invention are further illustrated below in conjunction with embodiments.

[0154] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with examples. However, it should be understood that the examples of the present invention are only for explaining the present invention, not for limiting the present invention, and the examples of the present invention are not limited to the examples given in the specification. The specific experimental conditions or operating conditions not specified in the examples are made under conventional conditions, or are made under the conditions recommended by the material supplier.

[0155] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0156] In the following examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.

[0157] A is PLA-1, purchased from Nature Works Ingeo 6260D;

[0158] B-1 is PLA-2, purchased from Nature Works Ingeo 6060D;

[0159] B-2 is PBAT, purchased from Huafeng HF 101;

[0160] C-1 is an anti-hydrolysis agent, a monomeric carbodiimide, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0161] C-2 is an anti-hydrolysis agent, a polymeric carbodiimide, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0162] C-3 is an anti-hydrolysis agent, diepoxy glycidyl ester, purchased from Hubei Xinjing S-182;

[0163] C-4 is an anti-hydrolysis agent, glycidyl isocyanate, purchased from Aladdin Mall;

[0164] D-1 is an antioxidant, a hindered amine antioxidant, purchased from Kain Chemical Irganox 1010;

[0165] D-2 is an antioxidant, a phosphite antioxidant, purchased from Kain Chemical Irganox 168;

[0166] E-1 is a nucleating agent, zinc phenyl phosphate, purchased from Shanxi Chemical Research Institute;

[0167] E-2 is a nucleating agent, adipic acid phenyl dihydrazide, purchased from Shanxi Chemical Research Institute;

[0168] F-1 is a processing aid, industrial 32# white oil;

[0169] F-2 is a processing aid, ethylene bisstearamide;

[0170] F-3 is a processing aid, calcium stearate;

[0171] Example 1

[0172] 1) A, C-1, D-1, D-2, E-1, F-1, F-2, and F-3 are uniformly mixed in the proportions of 97.7%, 0.5%, 0.15%, 0.2%, 1%, 0.1%, 0.3%, and 0.05% to obtain a core layer material; B-1, C-1, D-1, D-2, E-1, F-1, F-2, and F-3 are uniformly mixed in the proportions of 97.7%, 0.5%, 0.15%, 0.2%, 1%, 0.1%, 0.3%, and 0.05% to obtain a skin layer material.

[0173] 2) Feed the core layer raw material and the skin layer raw material into the corresponding core layer screw and skin layer screw respectively, after melting, filtering, metering, distribution, and finally extruding through the die head to obtain the primary fiber with skin-core structure. The core layer melting temperature is 220℃, the pipeline transportation and metering temperature is 230℃, and the extrusion temperature is 235℃; the skin layer melting temperature is 210℃, the pipeline transportation and metering temperature is 220℃, and the extrusion temperature is 235℃. The spinneret hole diameter is 0.6mm, the aspect ratio is 4:1, and the skin-core ratio is skin: core = 4:6. 3) After the primary fiber is air-cooled and stretched by positive pressure airflow, it is evenly laid on the mesh curtain under the action of suction. Among them, the side blowing wind temperature is 20℃, the wind speed is 1.2m / s, the humidity is 80%RH, the positive pressure stretching air pressure is 0.35Mpa, and the stretching speed is 4200-4500m / s. 4) The unconsolidated web is transported into a hot air oven, where the skin material is melted and bonded by the hot air, and then cooled and consolidated by a cold roller.

[0174] The hydrolysis-resistant biodegradable nonwoven fabric is obtained, wherein the hot air temperature is 125°C, the hot air pressure is 0.03Mpa, and the cooling water temperature of the cold roller is 7°C.

[0175] The non-woven fabric has a gram weight of 80gsm, an average pore size of 18-30 microns, and an air permeability of 3000-3500L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7d is 89%, 14d is 77%, 28d It is 53%.

[0176] Example 2

[0177] 1) A, C-1, D-1, D-2, E-2, F-1, F-2, and F-3 are uniformly mixed in the proportions of 97.2%, 1%, 0.15%, 0.2%, 1%, 0.1%, 0.3%, and 0.05% to obtain a core layer material; B-1, C-1, D-1, D-2, E-2, F-1, F-2, and F-3 are uniformly mixed in the proportions of 97.2%, 1%, 0.15%, 0.2%, 1%, 0.1%, 0.3%, and 0.05% to obtain a skin layer material.

[0178] 2) Feed the core layer raw material and the skin layer raw material into the corresponding screw respectively, after melting, filtering, metering, distribution, and finally extruding through the die head to obtain the primary fiber with skin-core structure. The melting temperature of the core layer is 220℃, the pipeline transportation and metering temperature is 230℃, and the extrusion temperature is 235℃; the melting temperature of the skin layer is 210℃, the pipeline transportation and metering temperature is 220℃, and the extrusion temperature is 235℃. The spinneret hole diameter is 0.6mm, the aspect ratio is 4:1, and the skin-core ratio is skin: core = 4:6.

[0179] 3) After being air-cooled and stretched by positive pressure airflow, the nascent fibers are evenly laid on the mesh curtain under the action of suction.

[0180] The blowing air temperature is 20℃, the wind speed is 1.2m / s, the humidity is 80%RH, the positive pressure drafting air pressure is 0.33Mpa, and the drafting speed is 4000~4300m / s. 4) The unconsolidated fiber web is transported into the hot air oven. Under the action of hot air, the skin material is melted and bonded, and then cooled and consolidated by the cold roller.

[0181] The hydrolysis-resistant biodegradable nonwoven fabric is obtained, wherein the hot air temperature is 125°C, the hot air pressure is 0.03Mpa, and the cooling water temperature of the cold roller is 7°C.

[0182] The nonwoven fabric has a gram weight of 60gsm, an average pore size of 20-35 microns, and an air permeability of 3500-4300L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7d is 95%, 14d is 90%, 28d is 80%.

[0183] Example 3

[0184] 1) A, C-1, D-1, D-2, F-1, and F-3 are mixed evenly in the proportions of 86.5%, 10%, 1%, 1%, 1%, and 0.5%, and then blended and extruded to obtain a core layer anti-hydrolysis masterbatch; wherein the aspect ratio of the twin screw is 44:1; there are 10 heating zones, the extrusion temperature is set to 165, 170, 180, 185, 185, 185, 185, 185, 185°C, and the screw speed is 150-250r / min; A, D-1, D-2, E-2, F-1, F-2, and F-3 are mixed evenly in the proportions of 66.2%, 1%, 1%, 20%, 1.2%, 10%, and 0.6%, and then blended and extruded to obtain a core layer nucleating masterbatch; wherein the aspect ratio of the twin screw is 44:1; there are 10 heating zones,

[0185] The extrusion temperature was set to 165, 170, 180, 185, 190, 190, 190, 185, 185, 185°C, and the screw speed was 200-300 r / min; 2) B-1, C-1, D-1, D-2, F-1, and F-3 were mixed uniformly in the proportions of 86.5%, 10%, 1%, 1%, 1%, and 0.5%.

[0186] The skin layer anti-hydrolysis masterbatch is obtained by blending and extruding; wherein the aspect ratio of the twin screw is 44:1; there are 10 heating zones, the extrusion temperature is set to 120, 125, 130, 140, 140, 140, 140, 140, 140°C, and the screw speed is 150-250r / min; B-1, D-1, D-2, E-2, F-1, F-2, and F-3 are uniformly mixed in the proportions of 66.2%, 1%, 1%, 20%, 1.2%, 10%, and 0.6%, and then blended and extruded to obtain the skin layer nucleating masterbatch; wherein the aspect ratio of the twin screw is 44:1; there are 10 heating zones,

[0187] The extrusion temperature is set to 120, 125, 130, 140, 145, 145, 140, 140, 140°C, and the screw speed is 200-300r / min;

[0188] 3) 8% core layer anti-hydrolysis masterbatch, 5% core layer nucleation masterbatch, and 87% A are fed into the core layer screw through a batching machine; 8% skin layer anti-hydrolysis masterbatch, 5% skin layer nucleation masterbatch, and 87% B-1 are fed into the skin layer screw through a batching machine, and after melting, filtering, metering, and distribution, the fibers are finally extruded through a die head to obtain a primary fiber with a skin-core structure. The core layer melting temperature is 220°C, the pipeline transportation and metering temperature is 230°C, and the extrusion temperature is 235°C; the skin layer melting temperature is 210°C, the pipeline transportation and metering temperature is 220°C, and the extrusion temperature is 235°C. The spinneret hole diameter is 0.6mm, the aspect ratio is 4:1, and the skin-core ratio is skin: core = 4:6. 4) After air cooling and positive pressure airflow drawing, the primary fiber is evenly spread on the mesh curtain under the action of suction. The side-blowing temperature is 20°C, the wind speed is 1.2m / s, the humidity is 80%RH, the positive drafting pressure is 0.35Mpa, and the drafting speed is 4200-4500m / s. 5) The unconsolidated web is transported into the hot air oven. Under the action of the hot air, the skin material is melted and bonded, and then cooled and consolidated by the cold roller.

[0189] The hydrolysis-resistant biodegradable nonwoven fabric is obtained, wherein the hot air temperature is 125°C, the hot air pressure is 0.03Mpa, and the cooling water temperature of the cold roller is 7°C.

[0190] The non-woven fabric has a gram weight of 80gsm, an average pore size of 20-30 microns, and an air permeability of 3100-3700L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7d is 94%, 14d is 89%, 28d It is 79%.

[0191] Example 4

[0192] The skin-core ratio is skin:core=5:5, the drawing air pressure is 0.33 MPa, the drawing speed is 4000-4200 m / s, the hot air temperature is 124°C, and the rest is the same as in Example 3.

[0193] The non-woven fabric has a gram weight of 80gsm, an average pore size of 20-30 microns, and an air permeability of 2600-3400L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7d is 93%, 14d is 87%, 28d is 75%.

[0194] Example 5

[0195] 1) Mix A, C-1, D-1, D-2, E-2, F-1, and F-3 at 97.7%, 0.8%, 0.15%, 0.2%, 1%, 0.1%, and 0.05

[0196] Mix evenly in proportion to obtain the core layer raw material; mix B-2, C-2, D-1, D-2, E-1, F-1, and F-3 in proportions of 97.7%, 0.8%, 0.15%, 0.2%, 1%, 0.1%, and 0.05 to obtain the skin layer raw material.

[0197] 2) Feed the core layer raw material and the skin layer raw material into the screw respectively, after melting, filtering, metering, distribution, and finally extruding through the die head to obtain the primary fiber with skin-core structure. The core layer melting temperature is 220℃, the pipeline transportation and metering temperature is 230℃, and the extrusion temperature is 235℃; the skin layer melting temperature is 190℃, the pipeline transportation and metering temperature is 210℃, and the extrusion temperature is 235℃. The spinneret hole diameter is 0.8mm, the aspect ratio is 4:1, and the skin-core ratio is skin: core = 4:6.

[0198] 3) After being air-cooled and stretched by positive pressure airflow, the nascent fibers are evenly laid on the mesh curtain under the action of suction. The side-blowing wind temperature is 16°C, the wind speed is 1.5m / s, the humidity is 80%RH, the positive pressure stretching air pressure is 0.32Mpa, and the stretching speed is 4000-4200m / s. 4) The unconsolidated fiber web is transported into the hot air oven. Under the action of hot air, the skin material is melted and bonded, and then cooled and consolidated by the cold roller.

[0199] The hydrolysis-resistant biodegradable nonwoven fabric is obtained, wherein the hot air temperature is 95°C, the hot air pressure is 0.03Mpa, and the cooling water temperature of the cold roller is 7°C.

[0200] The non-woven fabric has a gram weight of 80gsm, an average pore size of 20-30 microns, and an air permeability of 2600-3500L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7dis 90%, 14d is 86%, 28d It is 77%.

[0201] Example 6

[0202] C-3 is added to the core layer raw material formula and the skin layer raw material formula at a ratio of 1%, and the rest is the same as in Example 1;

[0203] The non-woven fabric has a gram weight of 80gsm, an average pore size of 20-30 microns, and an air permeability of 3000-3600L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7d is 90%, 14d is 79%, 28d It is 57%.

[0204] Example 7

[0205] C-4 is added to the core layer raw material formula and the skin layer raw material formula, and the proportion is 0.5%, and the rest is the same as in Example 1;

[0206] The nonwoven fabric has a gram weight of 80gsm, an average pore size of 23-40 microns, and an air permeability of 3500-4500L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7d is 90%, 14d is 80%, 28d is 60%.

[0207] Comparative Example 1

[0208] 1) A and B-1 are melted, filtered, metered, and distributed respectively, and finally extruded through a die head to obtain a primary fiber with a skin-core structure. The core layer melting temperature is 220°C, the pipeline transportation and metering temperature is 230°C, and the extrusion temperature is 240°C; the skin layer melting temperature is 210°C, the pipeline transportation and metering temperature is 220°C, and the extrusion temperature is 240°C. The spinneret hole diameter is 0.6mm, the aspect ratio is 4:1, and the skin-core ratio is skin: core = 4:6.

[0209] 2) After being air-cooled and stretched by positive pressure airflow, the nascent fibers are evenly laid on the mesh curtain under the action of suction. The side-blowing wind temperature is 20°C, the wind speed is 1.2m / s, the humidity is 80%RH, the positive pressure stretching air pressure is 0.35Mpa, and the stretching speed is 4200-4500m / s. 3) The unconsolidated fiber web is transported into the hot air oven. Under the action of hot air, the skin material is melted and bonded, and then cooled and consolidated by the cold roller.

[0210] The hydrolysis-resistant biodegradable nonwoven fabric is obtained, wherein the hot air temperature is 125°C, the hot air pressure is 0.03Mpa, and the cooling water temperature of the cold roller is 7°C.

[0211] The non-woven fabric has a gram weight of 80gsm, an average pore size of 18-30 microns, and an air permeability of 3000-3500L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7d is 4%, 14d is 0%.

[0212] Comparative Example 2

[0213] 1) Selecting the core layer anti-hydrolysis masterbatch and the skin layer anti-hydrolysis masterbatch prepared in Example 3,

[0214] 2) 5% core layer anti-hydrolysis masterbatch and 95% A are fed into the core layer screw through a weight-loss batching machine; 5% skin layer anti-hydrolysis masterbatch and 95% B-1 are fed into the skin layer screw through a weight-loss batching machine, and after melting, filtering, metering, and distribution, the fibers are finally extruded through a die head to obtain a primary fiber with a skin-core structure. The core layer melting temperature is 220°C, the pipeline transportation and metering temperature is 230°C, and the extrusion temperature is 240°C; the skin layer melting temperature is 210°C, the pipeline transportation and metering temperature is 220°C, and the extrusion temperature is 240°C. The spinneret hole diameter is 0.6mm, the aspect ratio is 4:1, and the skin-core ratio is skin: core = 4:6.

[0215] 3) After being air-cooled and stretched by positive pressure airflow, the nascent fibers are evenly laid on the net curtain under the action of suction. The side-blowing wind temperature is 20°C, the wind speed is 1.2m / s, the humidity is 80%RH, the positive pressure stretching air pressure is 0.35Mpa, and the stretching speed is 4200-4500m / s. 4) The unconsolidated fiber web is transported into the hot air oven. Under the action of hot air, the skin material is melted and bonded, and then cooled and consolidated by the cold roller.

[0216] The hydrolysis-resistant biodegradable nonwoven fabric is obtained, wherein the hot air temperature is 125°C, the hot air pressure is 0.033Mpa, and the cooling water temperature of the cold roller is 7°C.

[0217] The non-woven fabric has a gram weight of 80gsm, an average pore size of 20-30 microns, and an air permeability of 3000-3500L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7d is 89%, 14d is 75%, 28d It is 53%.

[0218] Comparative Example 3

[0219] 1) Select the core layer nucleation masterbatch and the skin layer nucleation masterbatch prepared in Example 3,

[0220] 2) 5% core layer nucleation masterbatch and 95% A are fed into the core layer screw through a weight-loss batching machine; 5% skin layer nucleation masterbatch and 95%

[0221] B-1 is fed into the cortex screw by a weight-loss batching machine, and after melting, filtering, metering, and distribution, it is finally extruded through a die head to obtain a primary fiber with a core-skin structure. The core layer melting temperature is 220°C, the pipeline transportation and metering temperature is 230°C, and the extrusion temperature is 240°C; the cortex melting temperature is 210°C, the pipeline transportation and metering temperature is 220°C, and the extrusion temperature is 240°C. The spinneret hole diameter is 0.6mm, the aspect ratio is 4:1, and the skin-core ratio is skin: core = 5:5.

[0222] 3) After being air-cooled and stretched by positive pressure airflow, the nascent fibers are evenly laid on the net curtain under the action of suction. The side-blowing wind temperature is 20°C, the wind speed is 1.2m / s, the humidity is 80%RH, the positive pressure stretching air pressure is 0.33Mpa, and the stretching speed is 4000-4200m / s. 4) The unconsolidated fiber web is transported into the hot air oven. Under the action of hot air, the skin material is melted and bonded, and then cooled and consolidated by the cold roller.

[0223] The hydrolysis-resistant biodegradable nonwoven fabric is obtained, wherein the hot air temperature is 125°C, the hot air pressure is 0.033Mpa, and the cooling water temperature of the cold roller is 7°C.

[0224] The non-woven fabric has a gram weight of 80gsm, an average pore size of 20-35 microns, and an air permeability of 3000-4000L / m 2 *S, hydrolysis aging test, the MD direction breaking strength retention rate is: η 7d is 7%, 14d is 0%.

[0225] Comparative Example 4

[0226] 1) A and B-2 are respectively melted, filtered, metered, and distributed, and finally extruded through a die head to obtain a primary fiber with a skin-core structure. The core layer melting temperature is 220°C, the pipeline transportation and metering temperature is 230°C, and the extrusion temperature is 235°C; the skin layer melting temperature is 190°C, the pipeline transportation and metering temperature is 210°C, and the extrusion temperature is 235°C. The spinneret hole diameter is 0.8mm, the aspect ratio is 4:1, and the skin-core ratio is skin: core = 4:6.

[0227] 2) After being air-cooled and stretched by positive pressure airflow, the nascent fibers are evenly laid on the net curtain under the action of suction. The side-blowing wind temperature is 16°C, the wind speed is 1.5m / s, the humidity is 85%RH, the positive pressure stretching air pressure is 0.32Mpa, and the stretching speed is 4000-4200m / s. 3) The unconsolidated fiber web is transported into the hot air oven. Under the action of hot air, the skin material is melted and bonded, and then cooled and consolidated by the cold roller.

[0228] The hydrolysis-resistant biodegradable nonwoven fabric is obtained, wherein the hot air temperature is 95°C, the hot air pressure is 0.03Mpa, and the cooling water temperature of the cold roller is 7°C.

[0229] The non-woven fabric has a gram weight of 80gsm, an average pore size of 20-30 microns, and an air permeability of 2500-3500L / m2*S. The hydrolysis aging test shows that the MD direction breaking strength retention rate is: η 7d is 75%, 14d is 65%, 28d It is 34%.

[0230] Table 1

[0231]

[0232] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.

[0233] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A hydrolysis-resistant biodegradable melt-spun nonwoven fabric, characterized in that: The non-woven fabric is composed of biodegradable fibers, and the fibers have a two-component core-skin structure of a fiber core layer and a fiber skin layer, wherein the melting point of the core layer polymer constituting the fiber core layer is higher than the melting point of the skin layer polymer constituting the fiber skin layer; the fibers also include an anti-hydrolysis agent, an antioxidant, a nucleating agent and a processing aid.

2. The hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to claim 1, characterized in that: The core layer polymer is selected from any one of the first polylactic acid and the blend of the first polylactic acid and PHA; And / or, the skin layer polymer is selected from any one of a second polylactic acid, PHA, and PBAT; And / or, the anti-hydrolysis agent is selected from one or a combination of monoepoxy glycidyl ester, diepoxy glycidyl ester, epoxy soybean oil, isocyanate glycidyl ester, monomeric carbodiimide, aliphatic carbodiimide and aromatic carbodiimide; And / or, the antioxidant is selected from at least one of hindered phenol compounds, phosphite compounds, amine compounds and thioether compounds; And / or, the nucleating agent is selected from at least one of an inorganic nucleating agent, an organic phosphate nucleating agent, an amide nucleating agent, and a hydrazide nucleating agent; And / or, the processing aid is selected from at least one of stearyl glyceryl, oleamide, ethylene bisstearamide, erucamide, barium stearate, calcium stearate, magnesium stearate, polyethylene wax, polyethylene glycol, and industrial white oil.

3. The hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to claim 1, characterized in that: Calculated by the weight percentage of the components in the fiber, the fiber core layer accounts for 35% to 80% of the total fiber weight, preferably 40% to 70%; and / or, calculated as a percentage of the weight of the components in the fiber, the fiber cortex accounts for 20% to 65% of the total weight of the fiber, preferably 30% to 60%; And / or, calculated as a percentage of the weight of the component in the fiber, the anti-hydrolysis agent accounts for 0.5% to 2% of the total weight of the fiber, preferably 0.8% to 1.5%; and / or, calculated as a percentage of the weight of the component in the fiber, the antioxidant accounts for 0.01% to 2% of the total weight of the fiber, preferably 0.03% to 1%; and / or, calculated as a percentage of the weight of the component in the fiber, the nucleating agent accounts for 0.1% to 14% of the total weight of the fiber, preferably 0.5% to 8%; And / or, calculated as a percentage of the weight of the component in the fiber, the processing aid accounts for 0.04% to 2%, preferably 0.07% to 1%, of the total weight of the fiber.

4. The hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to claim 1, characterized in that: The anti-hydrolysis agent and antioxidant are present in both the fiber core layer and the fiber sheath layer, and the types and amounts of the anti-hydrolysis agent and antioxidant in the fiber core layer and the fiber sheath layer can be the same or different; And / or, the nucleating agent and processing aid may be present in both the fiber core layer and the fiber sheath layer, or may be present only in the fiber core layer or the fiber sheath layer, and the types and amounts of the nucleating agent and processing aid in the fiber core layer and the fiber sheath layer may be the same or different.

5. The hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to claim 1, characterized in that: The diameter of the fiber is 1 to 100 μm, preferably 10 to 50 μm, more preferably 15 to 30 μm; And / or, the linear density of the fiber is 0.9 to 11.9 dtex, preferably 2.2 to 9.9 dtex, and more preferably 3.1 to 8.7 dtex.

6. The hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to claim 1, characterized in that: The nonwoven fabric has a gram weight of 10 to 300 g / m 2 , preferably 20 to 200 / m 2 , more preferably 30 to 150 g / m 2 ; and / or, the thickness of the nonwoven fabric is 0.15 to 1 mm, preferably 0.27 to 0.85 mm, more preferably 0.4 to 0.7 mm; and / or, the nonwoven fabric has a breaking strength in the MD direction of 0.6 to 3 times, preferably 0.9 to 2.5 times, the gram weight; And / or, the nonwoven fabric has a breaking strength in the CD direction of 0.5 to 2.5 times, preferably 0.9 to 1.8 times, the gram weight; and / or, the pore size of the nonwoven fabric is less than 75 μm, preferably less than 40 μm; And / or, the nonwoven fabric meets the biodegradability standard of GB / T19277.

7. The method for preparing the hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: 1) mixing a core layer polymer, an antioxidant, an anti-hydrolysis agent, a nucleating agent and a processing aid in a proportion to obtain a fiber core layer raw material; mixing a skin layer polymer, an antioxidant, an anti-hydrolysis agent, a nucleating agent and a processing aid in a proportion to obtain a fiber skin layer raw material; 2) melting, filtering, metering, distributing and extruding the core layer raw material and the skin layer raw material through a screw respectively to prepare a biodegradable primary fiber having a double-component core-skin structure with a fiber core layer and a fiber skin layer; 3) After air cooling and air flow drawing and orientation, the nascent fibers are randomly and evenly laid on the forming mesh curtain under the action of a suction fan to obtain an unconsolidated nonwoven fabric; 4) The unconsolidated nonwoven fabric is consolidated by hot air to obtain the nonwoven fabric.

8. The method for preparing a hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to claim 7, wherein in step 1), a portion of the core layer polymer, an antioxidant, an anti-hydrolysis agent, a nucleating agent and a processing aid are first blended to preform a core layer masterbatch; and the core layer masterbatch is then mixed with the remaining portion of the core layer polymer to obtain a core layer raw material; wherein, Calculated according to the weight percentage of the core layer raw material weight, the core layer masterbatch accounts for 5 to 40%; And / or, in step 1), firstly, a part of the skin polymer, antioxidant, anti-hydrolysis agent, nucleating agent and processing aid are blended to preform a skin masterbatch; then the skin masterbatch is mixed with the remaining part of the skin polymer; wherein, calculated as a weight percentage of the weight of the skin raw material, the proportion of the skin masterbatch is 5-40%; and / or, in step 2), for the core layer raw material, the melting temperature is 200-250° C.; And / or, in step 2), for the skin layer raw material, the melting temperature is 140-230°C; And / or, in step 2), the filtration mesh size is 250 to 400 mesh; And / or, in step 2), the spun fiber has a skin-core structure, the ratio of the area of ​​the fiber core layer to the area of ​​the fiber skin layer is 40 / 60 to 70 / 30; the diameter of the spun fiber is 0.22 to 1 mm; And / or, in step 3), the air cooling is provided by a side blowing device, the side blowing air temperature is 10-30° C., the wind speed is 0.1-6 m / s, and the humidity is 65-97% RH; And / or, in step 3), the drafting wind pressure is 0.2-0.45 MPa; And / or, in step 4), the unconsolidated fiber web is transported to a hot air oven through a mesh curtain, and under the action of the hot air penetration in the oven, the cortex of the two-component fiber melts and bonds with adjacent fibers to obtain a consolidated non-woven fabric without tangles; wherein the temperature of the hot air oven is 90-160°C.

9. A method for evaluating the hydrolysis resistance of a nonwoven fabric, characterized in that: Using the hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to any one of claims 1 to 6, the method for evaluating the hydrolysis resistance of the nonwoven fabric comprises the following steps: a) According to the requirements of GB / T 24218.3, cut non-woven fabric strips along the MD direction; b) Place the cut specimen in a container filled with 1.5±0.2 times its weight of pure water and seal it. To ensure that the specimen is completely immersed, a hydrophilic treatment agent of ≤1% may be added to the pure water, or manual intervention may be performed; c) Place the sealed sample in a constant temperature and humidity chamber and age it for n days at 54±2℃ and 75±5%RH; d) According to GB / T 24218.3, the initial breaking strength S0 and the breaking strength S0 after aging for n days were tested respectively. n ; e) Calculate the sample breaking strength retention rate η n , where η n =S n / S0*100%, n-aging days.

10. Use of the hydrolysis-resistant biodegradable melt-spun nonwoven fabric according to any one of claims 1 to 6 in the field of industrial filtration.

Citation Information

Patent Citations

  • Polylactic acid composition

    CN102712802B

  • Double-component heavy-denier spun-bonded non-woven fabric made of filaments

    CN103741374A

  • Polylactic acid hydrolysis-resisting fibre and preparation method thereof

    CN101240464A

  • Polylactic acid fiber with skin-core structure and full polylactic acid composite board

    CN107553855A

  • Biodegradable nonwoven fabric having excellent hydrolysis resistance

    JP2007023444A